2016
DOI: 10.1073/pnas.1523575113
|View full text |Cite
|
Sign up to set email alerts
|

Aurone synthase is a catechol oxidase with hydroxylase activity and provides insights into the mechanism of plant polyphenol oxidases

Abstract: Tyrosinases and catechol oxidases belong to the family of polyphenol oxidases (PPOs). Tyrosinases catalyze the o-hydroxylation and oxidation of phenolic compounds, whereas catechol oxidases were so far defined to lack the hydroxylation activity and catalyze solely the oxidation of o-diphenolic compounds. Aurone synthase from Coreopsis grandiflora (AUS1) is a specialized plant PPO involved in the anabolic pathway of aurones. We present, to our knowledge, the first crystal structures of a latent plant PPO, its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 65 publications
2
109
0
11
Order By: Relevance
“…81 Naringenin chalcones are also the building blocks for the biosynthesis of aurone compounds by a plant catechol oxidase, aurone synthase (AURS). 90 These conversions from chalcones to flavanones or aurones could also be realized by chemical reactions, such as the Algar–Flynn–Oyamada reaction. 91 …”
Section: Synthesismentioning
confidence: 99%
“…81 Naringenin chalcones are also the building blocks for the biosynthesis of aurone compounds by a plant catechol oxidase, aurone synthase (AURS). 90 These conversions from chalcones to flavanones or aurones could also be realized by chemical reactions, such as the Algar–Flynn–Oyamada reaction. 91 …”
Section: Synthesismentioning
confidence: 99%
“…Sellés-Marchart et al (2007) noted that trypsin activation of PPO from loquat fruit altered the pH range of the enzyme. A set of protein domain-swap experiments by Leufken et al (2015) have shown that this response may be associated with the C-terminal region of the protein suggesting that this domain (attached to the N-terminal region by a flexible linker domain) may physically block access to the active site of the enzyme under certain pH conditions (Boeckx et al 2015;Molitor et al 2016).…”
Section: Biochemistry Of Oxidative Discolourationmentioning
confidence: 99%
“…The chalcone specificity of that PPO was rationalized by its insufficient binding affinity for tyrosine or tyramine (Molitor, Mauracher, & Rompel, 2016), an effect that can explain the observed shift in the M/D ratio for cp48.…”
Section: Determination Of Kinetic Characters and Substrate Specificitymentioning
confidence: 99%